KARAKTERISASI LAPISAN OKSIDA HASIL ANODIZING PADA ALUMINIUM DENGAN VARIABEL WAKTU PENCELUPAN - Andika Wisnujati; Ferriawan Yudhanto (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
Anodizing is an electrolytic coating process that converts aluminum into aluminum oxide. The anodizing process is widely used in the manufacturing industry, especially in automotive components. Its utilization has benefits such as resistance to scratches, ease of maintenance, and added decorative value. The purpose of this study was to determine the effect of time variations on the hardness and thickness of the oxide layer in the 6xxx series of aluminum anodizing processes. The variation of time used in the immersion process is 20, 30, and 40 minutes, with an electric current of 2 amps and a voltage of 24 volts. After that, the dyeing and sealing process is carried out. The tests carried out included testing of hardness (Vickers) and the thickness of the oxide layer (coating thickness gauge). The results of the highest hardness test of 112.9 VHN were obtained at a time variation of 40 minutes, with an average layer thickness of 5.07 m. It can be said that the amount of time spent in the anodizing process has an effect on how hard the oxide layer gets and how thick it is on the 6xxx series of aluminum metal. Â